Embodied cognition of the student mathematical imaginations in conceptual understanding of algebraic expression - I Dwijayanti; I K Budayasa; T Y E Siswono (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Development of imagination in education creates a continuous education process and always new. The aim of research to describe of the student mathematical imagination and embedied cognition in conseptual understanding of algebraic expression. Type of this research is explorative with qualitative descriptive approach. The study was conducted in SMP Negeri 2 Semarang, at the end of 2017 for 3 months. Subjects involved in the study is a student who has a visual learning style. Methods of data collection using tests, interviews and observations. Test of data validity of research result using time triangulation technique. The results of this study are as follows: 1) subject imagine variables as objects that she recognized, such as the number of objects in a box or tin; 2) subject imagines an example and not an example of algebraic expression when it will define the concept of algebraic expression; 3) subject using gesture representation of variables, coefficients or constants; gesture pointing and gestures of writing as embodied cognition of the mathematical imaginations used; 4) subjects using the utterance as embodied cognition of mathematical imagination used or as the embodiment of social interaction that he did to get a confirmation or approval of researchers.